Effects of Different Agitator Blades on the Production Process of Biopolymer WL Gum by Sphingomonas sp. WG - Li, Hui; Zhou, Wanlong; Wang, Jiqian; Zhu, Hu (Journal of Composites and Biodegradable Polymers, 2020)
The effects of three agitators with different blade shapes, including the commonly-used six-flat-blade disc turbine, six-curved-blade disc turbine, and six-arrow-blade disc turbine on the production of biopolymer WL gum by Sphingomonas sp. WG was investigated in detail. The experiments were performed at the agitation speeds ranging from 100 to 500 r/min. The results showed that the moderate agitation speed was conducive to cell growth and WL gum production when using the agitators with curved-blade and arrow-blade. The maximal cell growth and WL gum were obtained at 300 r/min and 400 r/min, respectively. The six-arrow-blade disc turbine yielded the highest cell growth (11.74 g/L), WL gum production (40.89 g/L), and broth viscosity (91.62 Pa•s) among the three agitators. A comparison of the mixing characteristics showed that the power consumption of a six-arrow-blade disc turbine was the lowest. Overall, the six-arrow-blade disc turbine is suitable for WL gum fermentation with low energy consumption and high WL gum yield and viscosity. This work provided valuable information for large-scale industrial production of biopolymer WL gum.